WORSHIP AS A HUMAN MOTIVATION IN ISLAMIC BEHAVING: Human Motivation in Behaving - Jesus Alberto, Matas Valero; Purnomo, Halim (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
Motivation in worship has an important role in the life of each individual who has a specific goal in all his activities. This research aims to explain the contribution of the power of worship values in behavior. This research method is qualitative with a library research approach. Methods of collecting and analyzing data from various compiled references, resulting in new scientific contributions. This research explained that the worship of each individual is able to foster self-awareness that they recognize as creatures of Allah SWT who were created as human beings who serve Him. Therefore, a person who obeys worship will always try to maintain his behavior well in solitude, society even when worshiping with the aim of expecting the pleasure of Allah SWT.